Effect of abutment tooth location on the accuracy of digital impressions obtained using an intraoral scanner for removable partial dentures - Sakamoto Kazuki; Wada Junichiro; Arai Yuki; Hayama Hironari; Ishioka Yurika; Kim Eung-Yeol; Kazama Ryunosuke; Toyoshima Yusuke; Wakabayashi Noriyuki (JAPAN PROSTHODONTIC SOC, 2025)
Purpose:To verify the effect of abutment tooth location on the accuracy of digital impressions obtained using an intraoral scanner (IOS) for removable partial dentures (RPDs).
Methods: The target abutment teeth included the left first premolar (#34), second molar (#37), and right second premolar (#45) in a mandibular Kennedy class II model and the left and right second molars (#37, #47) in a class III model. Only #37 was isolated from the remaining teeth by the mucosal area in both models. Digital impressions were obtained using a desktop scanner (reference data) and an IOS (IOS data; scanning origin #37; n=10). The general trueness based on the entire model superimposition (TG), local trueness (TL) of an individual tooth, and dimensional accuracy (coordinate and linear accuracy) of the IOS data of the target abutment teeth were compared (α=0.05).
Results: In both models, #37 showed significantly inferior TG (P<0.01), superior TL (P<0.01), and mesial coordinate displace-ment (P<0.01 and P<0.05 in class II and III models, respectively). Intra-model comparisons showed that #45 in the class II model and #47 in the class III model had significantly inferior linear accuracy (P<0.05 and P<0.01, respectively) and buccal coordinate displacement (P<0.05 and P<0.01, respectively) compared with the other target teeth.
Conclusions: In digital impressions of RPDs, isolation of abutment teeth by mucosal areas can reduce general trueness based on the entire dental arch and mesial tooth displacement, whereas increased distance from the scanning origin can adversely affect local trueness and dimensional accuracy.